Efficacy of Radiofrequency Ablation in Chronic Pain Management - Dhungel, Pragya; Dabadi, Sambardhan; Dhungel, Raju Raj; Gurung, Pritam; Shrestha, Resha; Acharya, Samir; Dhakal, Sudan; Shrestha, Pranaya; Rajbhandari, Pravesh (Nepal Journal of Neuroscience, 2022)
The aim of this study is to determine the efficacy of radiofrequency ablation in management of chronic pain. Radiofrequency ablation in pain management was done in 21 patients who were experiencing chronic pain in different regions of the body. Patients were divided into three groups according to region of pain i.e. chronic lower back pain, trigeminal neuralgia, and osteoarthritis. Pre-treatment and Post-treatment pain score were taken with numeric rating scale (NRS). Denervation was achieved in the pain originating region with the help of Cosman RFG-1A radiofrequency generator under fluoroscopy obtained from Axiom Artis U. The comparison between pre pain score and post pain score revealed the pain was almost nullified in 52% of the patients whereas in 33% it was reduced to tolerable levels and 15% still had some trouble, though pain was slightly reduced as compared before ablation. Radiofrequency ablation alleviated the pain in cases where oral medications were not enough and surgical management could not be done or had a failure.